Comparison of cellular-based therapies following a long-segmental peripheral nerve defect in a rat model - Emily L. Errante; Joseph Yunga Tigre; Ericka A. Schaeffer; Meredith C. Costello; Andrew J. Kloehn; Aiko Puerto; Aisha Khan; Yelena Pressman; Risset Silvera; Francisco J. Sanchez; Brian R. Noga; W. Dalton Dietrich; et al. (PLoS ONE, 2025)
Peripheral nerve injury (PNI) is characterized by a loss of cellular and axonal integrity, often leading to limited functional recovery and pain. Many PNIs are not amenable to repair with traditional techniques; however, cell therapies, particularly Schwann cells (SCs), offer the promise of neural tissue replacement and functional improvement. Exosomes, which carry cellular signaling molecules, can be secreted by SCs and have shown promise in PNI. Our laboratory has had success using SCs in preclinical and clinical treatment settings. Transplanted cells have several known limitations, which exosomes mitigate. To that end, the current study investigated if implanted SC-derived exosomes in conduits, conduits with SCs, reverse autograft, or empty conduits comparably improve axonal regeneration and pain outcomes 16-weeks after repair of a long gap PNI in adult rats. Results show that there were no differences between groups in the von Frey filament testing or in the Hargreaves test. Electrophysiological testing showed a significant difference between the injured (ipsilateral) and uninjured (contralateral) limbs while histological assessment showed a significant difference between axonal counts in different areas of the conduit. Based on the results of the current study, more research is needed to understand the therapeutic role of exosomes in PNI.